2018
DOI: 10.2340/16501977-2494
|View full text |Cite
|
Sign up to set email alerts
|

Validity and feasibility of a temperature sensor for measuring use and non-use of orthopaedic footwear

Abstract: LAY ABSTRACTOrthopaedic footwear is frequently prescribed to patients with a wide variety of pathologies, such as diabetes mellitus, rheumatoid arthritis, degenerative foot disorders and muscle disorders. For these patients, orthopaedic footwear is used for a range of serious foot and/or ankle problems; for example, to prevent the onset or recurrence of foot ulcers, to reduce pain, to support anatomical foot deformities, enhance stability and mobility, and redistribute plantar pressure. Orthopaedic footwear is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Bus el al introduced and validated a temperature‐based monitoring system called “@monitor”, which could be attached to the inner surface of an assistive device (eg, footwear) to determine duration of the use of the assistive device. Orthotimer sensor (Rollerwerk, Balingen, Germany) is an example of commercially available technologies, which is using a microsensor and a unique individual ID number. The sensor could be integrated in shoes, insoles, orthotic devices, and offloading and enables wear time to be measured.…”
Section: Technologies To Improve Adherence To Protected Footwearmentioning
confidence: 99%
See 1 more Smart Citation
“…Bus el al introduced and validated a temperature‐based monitoring system called “@monitor”, which could be attached to the inner surface of an assistive device (eg, footwear) to determine duration of the use of the assistive device. Orthotimer sensor (Rollerwerk, Balingen, Germany) is an example of commercially available technologies, which is using a microsensor and a unique individual ID number. The sensor could be integrated in shoes, insoles, orthotic devices, and offloading and enables wear time to be measured.…”
Section: Technologies To Improve Adherence To Protected Footwearmentioning
confidence: 99%
“…Bus el al 37 introduced and validated a temperature-based monitoring system called "@monitor", which could be attached to the inner surface of an assistive device (eg, footwear) to determine duration of the use of the assistive device. Orthotimer sensor (Rollerwerk, Balingen, Germany) 38 defined as daily hours of device wear, was determined using sensor data and patient questionnaires. They concluded that a real-time and comprehensive foot pressure alert method with a minimum number of alerts (one every 2 hours) are effective to allow optimal response to offloading cues from a smart insole system and for improving adherence to prescribed diabetic shoes over time.…”
Section: Technologies To Improve Adherence To Protected Footwearmentioning
confidence: 99%
“…More research on this topic is needed, to better understand how adherence to wearing therapeutic footwear can be improved. In these studies, adherence should be quantitatively monitored …”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that a temperature threshold of 25 • C to indicate that footwear was worn had a sensitivity of 95%, a specificity of 99%, a negative predictive value of 99% and a positive predictive value of 99% in determining footwear use [51]. Past research also demonstrates that these temperature sensors are a valid method of estimating footwear adherence compared to adherence measured using a time-lapse camera [52]. It is anticipated that small sensors will soon become available that can accurately monitor an individual's footwear use and activity and provide "live" data seamlessly to remotely located health practitioners [53].…”
Section: Offloading Footwear Adherence Monitoringmentioning
confidence: 99%
“…Further developments are needed before this approach can be implemented in a remote management program. It should be noted that there is a paucity of commercially available sensors for monitoring adherence easily and accurately, and most of the aforementioned sensors have only been used in a research context [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Offloading Footwear Adherence Monitoringmentioning
confidence: 99%